Assessing nominal income rules for monetary policy with model and data uncertainty - Glenn D. Rudebusch (European Central Bank (ECB), 2000)
Nominal income rules for monetary policy have long been debated, but two issues are of particular recent interest. First, there are questions about the performance of such rules over a range of plausible empirical models - especially models with and without rational inflation expectations. Second, there are questions about the performance of these rules in real time using the type of data is actually available contemporaneously to policymakers rather than final revised data. This paper determines optimal monetary policy rules in the presence of such model uncertainty and real-time data uncertainty and finds only a limited role for nominal output growth.
Keywords: E5; 330